Development of an Improved Pitaya Juice Processing System - Abd Rahman, Nur‘Aliaa (2009)
The processing of tropical fruit juice has improved nowadays. Dragon fruit or pitaya is one of the tropical fruits that has attracted the attention of consumers, fruit growers and also food processing industry entrepreneurs in this country. Various pitaya products have been marketed in Malaysia. Pitaya juice is well known for its health benefits. Since pitaya processing has just developed, more research should be carried out to increase the production quality of pitaya product such as fruit juice. In the current research, pitaya juice production operations were studied from the peeling process to the production of clear pitaya juice using enzyme. A fruits grater and peeler was invented to ease the peeling process before the fruit is processed into juice. The machine was able to reduce the peeling time up to 94% when compared to manual peeling. This apparatus was proven to ease and speed up the process of peeling pitaya skin. Studies were carried out to obtain the optimum processing condition for enzymatic clarification of red and white pitaya juices. Two types of commercial pectinase enzymes had been used which were Pectinex Ultra SP-L and Pectinex CLEAR. Response Surface Methodology (RSM) was used to obtain the optimum processing condition in terms of enzyme concentration, temperature and incubation period. The optimum processing condition for enzymatic treatment of red pitaya juice treated with Pectinex Ultra SP-L was found to be at 0.10% enzyme concentration at 40oC for 45 min. The optimum processing condition of red pitaya juice treated using Pectinex CLEAR was reported in other study. For white pitaya juice, the optimum processing condition for enzymatic treatment using Pectinex Ultra SP-L was at 0.06% enzyme concentration at 49oC for 40 min. For white pitaya juice treated with Pectinex CLEAR, the optimum processing condition was at 0.10% enzyme concentration at 40oC for 82 min. The use of this enzyme was proven to increase the recovery of pitaya juice after the filtration process. The data for pitaya composition after processing was also obtained. It was observed that several components such as protein and phenolic contents (antioxide component) had increased after the enzymatic treatment. Research was carried out further by developing a process flow sheet for producing pitaya juice at laboratory-scale (batch processing). Laboratory-scaled processing was carried out to resemble large-scaled continuous processing in the industry. Calculation of material balance was also done based on the process flow sheet that had been developed. Data obtained from this research can be used as a base for developing large-scale pitaya juice production process at industrial level.